In vitro experiment to elucidate the mechanism of the 'soft shell technique' for preventing subretinal migration of perfluoro-octane. Issue 3 (5th January 2017) - Chan, Yau Kei; Lu, Yongjie; Czanner, Gabriela; Wu, Jing; Cheng, Ho Ching; Hussain, Rumana; Sakamoto, Taiji; Shum, Ho Cheung; Wong, David
Abstract : Aim: Perfluorocarbon liquid (PFCL) can migrate into subretinal space in detached and stiffened retina with open holes during vitreoretinal surgery. An innovative 'soft shell' technique was introduced to reduce the complication using hyaluronate (HA) to 'cover' the retinal hole. This study aims to study the effectiveness of this technique in vitro. Methods: Ex vivo porcine retina was mounted on a transwell insert. Beneath the retina was an aqueous solution. Two retinal holes were made using needle punctures. One of the two retinal holes was covered with HA. Perfluoro-n-octane (PFO) was added above the retina incrementally using a syringe pump. The height of PFO required to cause the migration of PFO through the retinal holes was measured. The 'pendant drop' method was carried out to measure the interfacial tensions between the PFO and aqueous, and between PFO and four different concentrations of HA solution. Results: A statistically higher PFO level was required to cause the migration of PFO through the retinal hole with HA coating than without HA coating (Tobit regression with p<0.05). The use of HA was associated with 2.39-fold increase in hydrostatic pressure before the collapse of the PFO interface at the retinal holes. The interfacial tension between PFO and HA solution with concentrations of 0.05%, 0.25%, 0.5% and 1% were 54.2±0.6, 55.3±0.6, 59.5±1.5 and 68.3±1.3 mN/m, respectively (mean±SD). The interfacial tension between PFO and aqueous with 1% HA coating (68.3±1.3 mN/m) was significantly higher than that without (37.4±3.4 mN/m) (p<0.05). Conclusions: The interfacial tension between HA and PFO is higher than that between aqueous and PFO. This is a plausible physical explanation of how the 'soft shell' technique might work to prevent subretinal migration of PFCL.